The paradox of managing autonomy and control: An exploratory study - G. Gilbert; M. Sutherland (South African Journal of Business Management, 2013)
Managers are frequently offered conflicting advice as to how to increase organisational success. One of these complex dilemmas is whether to grant employees autonomy, which may lead to self-management and empowerment or alternatively, exercise control which may enable managers to retain a well-focussed and goal driven workforce. This research focuses on the key factors that influence the various combinations of autonomy and control and their respective outcomes. Qualitative exploratory research was conducted using in-depth interviews with 16 leading South African management and Human Resource experts to uncover their insights regarding this dilemma. The findings suggest that combinations of autonomy and control can co-exist. Management are able to create environments with high levels of autonomy whilst simultaneously retaining high levels of monitoring and oversight when the management control is indirect. It was found that the seemingly contradictory practices of autonomy versus control are a paradox, not a dilemma. Seventeen factors were identified that influence the different levels of autonomy and control in organisations.
Keywords: 650